2017
DOI: 10.1093/bja/aex005
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the systemic concentrations of local anaesthetic after transversus abdominis plane block and rectus sheath block

Abstract: Local anaesthetic in TAPB and RSB can lead to detectable systemic concentrations that exceed commonly accepted thresholds of LA systemic toxicity. Our study highlights that these techniques are relatively safe with regard to LA systemic toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 47 publications
3
39
1
4
Order By: Relevance
“…Ropivacaine has therefore become a popular choice for high‐dose, high‐volume fascial plane blocks including the TAP block. The risk of inadvertent intravenous, bowel or nerve injection is minimized by ultrasound guidance and needle aspiration before injection. In the present study, no patient had symptoms of local anaesthetic systemic toxicity (such as seizures, cardiovascular collapse, metallic taste, tinnitus) either immediately following blocks or after operation.…”
Section: Discussionmentioning
confidence: 59%
“…Ropivacaine has therefore become a popular choice for high‐dose, high‐volume fascial plane blocks including the TAP block. The risk of inadvertent intravenous, bowel or nerve injection is minimized by ultrasound guidance and needle aspiration before injection. In the present study, no patient had symptoms of local anaesthetic systemic toxicity (such as seizures, cardiovascular collapse, metallic taste, tinnitus) either immediately following blocks or after operation.…”
Section: Discussionmentioning
confidence: 59%
“…A recent meta-analysis demonstrated this by evaluating the systemic concentrations of LA after perioperative single-shot TAP or rectus sheath block, and demonstrated that 8.6% of patients had systemic concentrations that were above the commonly acceptable threshold for LAST. 51 The challenge facing anaesthesiologists caring for obstetric patients is to find a balance between utilising a LA that provides effective analgesia whilst minimising the risk of LAST. In pregnancy, enhanced sensitivity as a result of altered physiology may lead to an increased risk of LAST.…”
Section: Discussionmentioning
confidence: 99%
“…We used 10mM bupivacaine based on plasma concentrations measured after low-dose epidural infusion in labour, 21 and transversus abdominal plane blocks after Caesarean section. 22 This concentration is below levels associated with systemic effects 23 and toxicity (!17mM). 24…”
Section: Laboratory Experimentsmentioning
confidence: 95%